2021
DOI: 10.3390/ma14051152
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tooth- and Bone-Borne Appliances on the Stress Distributions and Displacement Patterns in the Facial Skeleton in Surgically Assisted Rapid Maxillary Expansion—A Finite Element Analysis (FEA) Study

Abstract: The aim of this study was to compare the reduced stresses according to Huber’s hypothesis and the displacement pattern in the region of the facial skeleton using a tooth- or bone-borne appliance in surgically assisted rapid maxillary expansion (SARME). In the current literature, the lack of updated reports about biomechanical effects in bone-borne appliances used in SARME is noticeable. Finite element analysis (FEA) was used for this study. Six facial skeleton models were created, five with various variants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Serious complications resulting from uncontrolled fractures of the facial skeleton and cranial base and damage to vascular and neural structures as a result of SARPE are rarely reported [19,[30][31][32]. It is now known that a maxillary incision along the Le Fort I line and separation at the palatal suture results in expansion without negative effects on distant structures of the facial skeleton and neurocranium [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Serious complications resulting from uncontrolled fractures of the facial skeleton and cranial base and damage to vascular and neural structures as a result of SARPE are rarely reported [19,[30][31][32]. It is now known that a maxillary incision along the Le Fort I line and separation at the palatal suture results in expansion without negative effects on distant structures of the facial skeleton and neurocranium [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the levels stress accumulation and displacement in the midpalatal and circummaxillary sutures were found in descending order as the bone-borne, tooth-borne, and hybrid groups [ 22 , 23 ]. Although bone anchorage was taken in the hybrid group, the findings of our study showed that better force transfer and displacement were achieved by providing more tooth anchorage in the tooth-borne group.…”
Section: Discussionmentioning
confidence: 99%
“…-Researches available only by abstracts; -Researches with unclear, poorly or inappropriate methods. Studies whose scope was relevant to the topic [20][21][22], but located outside the period of the search, were included and considered as complementary. These were used as a source of conceptual or illustrative bases in the body of the present study.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…Furthermore, it also helps in the planning and monitoring of orthognathic surgery, enabling the reproduction of operative predictability and allowing the observation of anatomical structures of relevance to surgery in a more detailed and expanded way [22].…”
Section: Computerized Spiral Tomography or Fan Beam (Ctfb)mentioning
confidence: 99%